Former Yugoslavia Through Documents : From its dissolution to the peace settlement: Part 2 - Trifunovska, Snežana, (International Law - Book Archive pre-2000., 1999)
From the end of the 1980s and beginning of the 1990s onwards, the world's attention has been occupied with the events which eventually led to the dissolution of the Socialist Federal Republic of Yugoslavia and to the creation of five independent and sovereign states. Apart from the humanitarian disaster and the devastated economies of the countries created on the territory of the former Yugoslavia, it brought some important issues of international law to the forefront, and provided the impetus for some new and rapid developments. The book is an epilogue to the first, very successful, collection Yugoslavia through Documents: from its creation to its dissolution , published by Martinus Nijhoff Publishers in 1994. However, because of the complexity of the issues in the political, military, humanitarian and legal fields, its structure is different. The book is divided into an Introduction and nine Parts, each of them dealing with specific issues and containing, where appropriate, the Editor's note, comment or additional information. These two volumes constitute an absolutely essential collection for all research libraries.